Effect of storage container and storage period on germination of grain maize in bako, West Shewa, Ethiopia - Negasa Fufa; Solomon Abera; Girma Demissie (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
Grain quality is in terms of heritably and physically pure whereas postharvest managements are used to increase grain/seed quality through seed processing while required storage condition maintain its quality. However, little information available on germination capacity of maize as affected by storage containers and period in Ethiopia. Thus, the aim of the study was to evaluate the effects of storage containers with storage period on germination of maize grain in the laboratory. The experiment was conducted between December 2017 and May 2018 in Bako, West Shawa, Ethiopia. The experiment was arranged in CRD designs with three replications. The treatments consist of two factors combinations with storage types (Gombisa, sack and Hermetic bag) and storage periods (0, 1, 2, 3, 4, 5, and 6) months. Germination test was done by the standard procedures of international seed test agency (ISTA). The collected data were analyzed statistically using Generalized Linear Model (GLM) procedure of SAS and means that were significantly different were separated using Least Significant Difference (LSD). The result showed significant different (P<0.05) interaction effect on germination. The values for initial loading were 98.0% and subsequently reduced 78.9% at the end of 6 months of storage. Initially, the highest 98.0% germination was recorded and reduced significantly (p<0.05) to 72.0, 76.0 and 88.6% for Gombisa, Sack and Hermetic bags, respectively. Hermetic bag kept significantly higher germination percentage with 94.2 % at six 6 months in storage, respectively as compared to the rest of the two storage containers. The reduction of germination of grain stored in Gombisa and Sack were due to the grain damaged by weevils (S. zeamais, S. granaries, T. castaneum and S. cerealella) and increment of moisture content due to insect infestation and mould growth. From this study, it can be concluded that maize grains which was stored for less than 4 months had shown better seed germination but variations were observed among the storage structures studied. Also, Hermetic bag storage showed better result with higher germination throughout the storage periods.